Negative electrode active material, negative electrode, nonaqueous electrolyte secondary battery, and method for producing negative electrode active material

CN123023142APending Publication Date: 2026-10-30LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580023145.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-12-26
Filing Date
2025-12-26
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0030]本发明可以提供一种用于改善二次电池循环特性的负极活性材料、负极、非水电解质二次电池以及该负极活性材料的制备方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123023142A_ABST
    Figure CN123023142A_ABST
Patent Text Reader

Abstract

The present invention provides a negative electrode active material for improving cycle characteristics of a secondary battery, a negative electrode, a nonaqueous electrolyte secondary battery, and a production method of the negative electrode active material. The production method of the negative electrode active material according to one embodiment includes a reduction step of reacting silicon oxide (SiO a , 0 < a ≤ 2) with magnesium (Mg), an acid treatment step of treating the reacted material with an acid, and a mechanical alloying step of mechanically alloying the reacted material until a crystallite size evaluated from a powder X-ray diffraction pattern is 10 nm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present invention relate to a negative electrode active material, a negative electrode, a non-aqueous electrolyte secondary battery, and a method for preparing the negative electrode active material.

[0002] This application is based on and claims priority to Japanese Patent Application No. 2024-231224, filed with the Japan Patent Office on December 26, 2024, the entire contents of which are incorporated herein by reference. Background Technology

[0003] Recently, there has been development on adding silicon oxide to the negative electrode active material of lithium-ion secondary batteries. For example, Patent Document 1 discloses adding lithium-predoped silicon oxide to the negative electrode active material.

[0004] [Existing Technical Documents]

[0005] [Patent Literature]

[0006] Patent Document 1: Japanese Patent Application Publication No. 2018-152250 Summary of the Invention

[0007] Technical issues

[0008] However, in anode materials with added silicon oxide, the lithium silicate phase generated during charging often reduces the initial efficiency. Furthermore, when lithium is pre-doped into silicon oxide as disclosed in Patent Document 1, the lithium silicate phase may lead to a reduction in battery capacity.

[0009] To address this problem, after careful study, the inventors discovered that when silicon oxide is reduced, the silicate phase decreases and a Si phase is generated, thereby improving capacity and initial efficiency. However, this discovery also revealed that the reduction process increases the crystallinity of the Si phase, leading to severe electrode expansion and consequently poor battery cycle characteristics.

[0010] The present invention aims to provide a negative electrode active material for improving the cycle characteristics of a secondary battery, a negative electrode, a non-aqueous electrolyte secondary battery, and a method for preparing the negative electrode active material.

[0011] Technical solution

[0012] The present invention may include the following embodiments.

[0013] [1] A negative electrode active material comprising: composite particles containing a Si phase and magnesium silicide oxide, Wherein, the crystallite size of the Si phase and the crystallite size of at least one phase contained in the magnesium silicide oxide, as evaluated by powder X-ray diffraction patterns, are less than 10 nm.

[0014] [2] The negative electrode active material as described in [1], wherein the magnesium silicide oxide contains at least one of Mg2SiO4 or MgSiO3.

[0015] [3] The negative electrode active material as described in [1] or [2], wherein at least one of the Si phase or magnesium silicide oxide contained in the composite particles is amorphous.

[0016] [4] The negative electrode active material as described in any one of [1] to [3], wherein, based on the total mass of the composite particles, the amount of Si phase contained in the composite particles is more than 20% by mass and less than 70% by mass.

[0017] [5] The negative electrode active material as described in any one of [1] to [4], wherein the composite particles substantially do not contain MgO.

[0018] [6] The negative electrode active material as described in any one of [1] to [5], wherein the surface of the composite particles is coated with a carbon-based material.

[0019] [7] The negative electrode active material as described in [6], wherein, based on the amount of composite particles (excluding the carbon material), the amount of carbon material used to coat the composite particles is 5% by mass or more and 20% by mass or less.

[0020] [8] A negative electrode comprising: a negative current collector, and

[0021] A negative electrode active material layer present on the negative electrode current collector, the negative electrode active material layer comprising any one of [1] to [7].

[0022] [9] A non-aqueous electrolyte secondary battery comprising the negative electrode described in [8].

[0023]

[10] A method for preparing a negative electrode active material, comprising: making silicon oxide (SiO2) a The reduction step in the reaction of magnesium (Mg) with metallic magnesium (0 < a ≤ 2); An acid treatment step involving treating the reacted material with acid; and The reacted material is mechanically alloyed until the crystallite size, as evaluated by powder X-ray diffraction, is less than 10 nm.

[0024]

[11] The method for preparing the negative electrode active material as described in

[10] , wherein the mechanical alloying is carried out by at least one means selected from the group consisting of planetary mill, rotary mill, vibratory mill, electric mill and stirred mill.

[0025]

[12] The method for preparing the negative electrode active material as described in

[10] or

[11] , wherein the mechanical alloying is carried out under an inert atmosphere.

[0026]

[13] The method for preparing the negative electrode active material as described in any one of

[10] to

[12] , wherein, in the acid treatment step, MgO is removed by reacting with acid.

[0027]

[14] A method for preparing a negative electrode active material as described in any one of

[10] to

[13] , wherein, in the reduction step, silicon oxide (SiO2) a At least a portion of ) is reduced to Si.

[0028]

[15] The method for preparing the negative electrode active material as described in any one of

[10] to

[14] further includes a coating step of coating the reacted material with a carbon-based material.

[0029] Beneficial effects

[0030] The present invention can provide a negative electrode active material for improving the cycle characteristics of a secondary battery, a negative electrode, a non-aqueous electrolyte secondary battery, and a method for preparing the negative electrode active material. Attached Figure Description

[0031] Figure 1 This is a diagram showing the powder X-ray diffraction patterns of Example 1, Example 2 and Comparative Example 1.

[0032] Figure 2 This is a graph showing the cycle characteristics of the button cells of Example 1, Comparative Example 1, and Comparative Example 2.

[0033] Figure 3 This is a graph showing the cycle characteristics of the button cells of Example 2, Comparative Example 3, and Comparative Example 4. Detailed Implementation

[0034] The following will describe the negative electrode active material, negative electrode, non-aqueous electrolyte secondary battery, and method for preparing the negative electrode active material according to embodiments. The following embodiments are provided to illustrate one embodiment of the present invention, but are not intended to be limiting; any modifications or alterations can be made within the technical scope of the present invention. Furthermore, various configurations and features in the embodiments can be combined arbitrarily.

[0035] 1. Non-aqueous electrolyte secondary battery

[0036] One embodiment of the present invention relates to a non-aqueous electrolyte secondary battery. The non-aqueous electrolyte secondary battery of this embodiment includes: a negative electrode, a positive electrode, a separator sandwiched between the negative electrode and the positive electrode, and a non-aqueous electrolyte. Specific examples of the secondary battery may include lithium-ion secondary batteries with advantages such as high energy density, discharge voltage, and output stability.

[0037] The following text will primarily describe the components of a lithium-ion secondary battery (negative electrode, positive electrode, separator, and non-aqueous electrolyte). However, this invention is not limited to lithium-ion secondary batteries and can be applied to various non-aqueous electrolyte secondary batteries.

[0038] 1-1. Negative electrode

[0039] 1-1-1. Components of the negative electrode

[0040] The negative electrode includes a negative current collector and a layer of negative active material on one or both sides of the negative current collector. The layer of negative active material may exist on all or part of the surface of the negative current collector.

[0041] negative current collector

[0042] The negative electrode current collector used for the negative electrode is not limited to a specific type and can be any material that does not cause chemical changes and is conductive in the battery. For example, the negative electrode current collector can include: copper; stainless steel; aluminum; nickel; titanium; sintered carbon; copper or stainless steel with a surface treated with carbon, nickel, titanium or silver; aluminum-cadmium alloy.

[0043] The thickness of the negative electrode current collector can range from 3 μm to 500 μm. The negative electrode current collector can have a finely textured surface to improve adhesion to the negative electrode active material. The negative electrode current collector can be in various forms, such as films, sheets, foils, meshes, porous bodies, foams, or nonwoven fabrics.

[0044] Negative electrode active material layer

[0045] The negative electrode active material layer may comprise a negative electrode active material, a binder, a conductive agent, and additives. For example, the negative electrode active material layer can be formed by coating a negative electrode active material slurry containing a mixture of the negative electrode active material, binder, and conductive agent dissolved or dispersed in a solvent onto a negative electrode current collector, drying the slurry, and then rolling it. Alternatively, the negative electrode active material layer can be formed by casting the negative electrode active material slurry onto a carrier, peeling the film off the carrier, and pressing the film layer onto the negative electrode current collector. Optionally, the mixture may further comprise any other additives, such as dispersants or fillers.

[0046] Negative electrode active materials

[0047] In the lithium-ion secondary battery of the embodiment, the negative electrode active material comprises composite particles containing a Si phase and magnesium silicide oxide. The crystallite size of the Si phase and the crystallite size of at least one phase contained in the magnesium silicide oxide, as evaluated by powder X-ray diffraction (XRD) patterns, are less than 10 nm.

[0048] The negative electrode active material layer may also contain a negative electrode active material different from the composite particles (e.g., carbon-based materials). In this specification, all materials that contribute to the charge-discharge reaction at the negative electrode are referred to as "negative electrode active materials".

[0049] Based on the total mass of the negative electrode active material layer, the content of the negative electrode active material can be from 80% to 99% by mass. Based on the total mass of the negative electrode active material, the content of the composite particles (excluding the carbon coating described below) can be, for example, 0.1% by mass or more and 99% by mass or less, 1% by mass or more and 90% by mass or less, 5% by mass or more and 50% by mass or less, or 10% by mass or more and 30% by mass or less.

[0050] Silicon (Si), which has the ability to intercalate lithium, can be responsible for the charge and discharge reaction at the negative electrode.

[0051] Based on the total mass of the composite particles, the amount of Si phase in the composite particles is 20% by mass or more and 70% by mass or less. When the amount of Si phase is 20% by mass or more, sufficient battery capacity can be obtained. When the amount of Si phase is 70% by mass or less, the expansion of the Si phase can be sufficiently suppressed by magnesium silicide oxide.

[0052] The crystallite size of the Si phase in the composite particles can be less than 10 nm, for example, it can be greater than 1 nm and less than 9 nm, greater than 2 nm and less than 8 nm, greater than 3 nm and less than 7 nm, or greater than 4 nm and less than 6 nm. In this specification, the crystallite size of the Si phase is the value calculated by Scherrer formula based on the full width at half maximum (FWHM) of the (111) peak of the Si phase in the powder XRD pattern.

[0053] When the crystallite size is below 10 nm, the expansion of the entire electrode during charging and discharging can be suppressed because the crystallite size of the Si phase is small enough. As a result, cracking caused by expansion and contraction can be suppressed, thereby improving the cycle characteristics of the secondary battery.

[0054] As described above, the composite particles may also contain magnesium silicide oxide. For example, magnesium silicide oxide includes at least one of MgSiO3 or Mg2SiO4, but is not limited thereto. Preferably, the composite particles consist of a Si phase and magnesium silicide oxide (which may contain unavoidable impurities).

[0055] Based on the total mass of the composite particles, the total amount of magnesium oxide silicide in the composite particles is, for example, 0.1% by mass or more and 20% by mass or less, 0.5% by mass or more and 10% by mass or less, or 1% by mass or more and 5% by mass or less. When the total amount of magnesium oxide silicide is 0.1% by mass or more, the magnesium oxide silicide can suppress the volume expansion of the Si phase. When the total amount of magnesium oxide silicide is 20% by mass or less, a sufficient increase in battery capacity through the Si phase can be obtained.

[0056] When the composite particles contain magnesium silicide oxide, the mass ratio of Si atoms to Mg atoms (Si / Mg) in the negative electrode active material is, for example, 10 or more and 50 or less, preferably 15 or more and 40 or less, and more preferably 20 or more and 30 or less. When the mass ratio (Si / Mg) is 10 or more, the greater amount of Si can lead to a higher energy density. When the mass ratio (Si / Mg) is 50 or less, it is believed that a sufficient reduction reaction occurs.

[0057] The crystallite size of the MgSiO3 phase in the composite particles can be less than 10 nm, for example, it can be greater than 0.5 nm and less than 8 nm, greater than 1 nm and less than 5 nm, greater than 1.5 nm and less than 4 nm, or greater than 2 nm and less than 3 nm. In this specification, the crystallite size of the MgSiO3 phase is the value calculated by Scherrer formula based on the full width at half maximum (FWHM) of the (310) peak of the MgSiO3 phase in the powder XRD pattern.

[0058] When the crystallite size is below 10 nm, the interface (grain boundary) between the Si phase and the MgSiO3 phase can be reduced due to the sufficiently small crystallite size, and the MgSiO3 phase can suppress the expansion of the Si phase. As a result, it may be possible to suppress cracking caused by expansion and contraction, thereby improving the cycle characteristics of the secondary battery.

[0059] At least one of the Si phase or magnesium silicide oxide in the composite particles can be amorphous. For example, at least one of the Si phase, MgSiO3 phase, or Mg2SiO4 phase is amorphous. For example, the MgSiO3 phase can be amorphous. Additionally, the Mg2SiO4 phase can be amorphous. When the Si phase is amorphous, the expansion of the Si phase can be sufficiently suppressed. When the MgSiO3 phase and / or the Mg2SiO4 phase are amorphous, the grain boundaries with the Si phase may substantially disappear, and the magnesium silicide phase can absorb the expansion of the Si phase, thereby suppressing damage to the electrode such as cracking caused by the expansion of the Si phase.

[0060] The composite particles may also contain magnesium oxide (MgO) and / or metallic magnesium (Mg). These may correspond to residues remaining after reduction or acid treatment as described below. However, preferably, the composite particles are substantially free of or almost free of magnesium oxide (MgO) and / or metallic magnesium (Mg). In this specification, "substantially free of or almost free of" means any peaks of the substance not clearly observed in the powder XRD pattern of the composite particles.

[0061] Based on the total mass of the composite particles, the amount of magnesium oxide (MgO) in the composite particles is, for example, less than 5% by mass, less than 1% by mass, less than 0.1% by mass, or less than 0.01% by mass. Based on the total mass of the composite particles, the amount of metallic magnesium (Mg) in the composite particles is less than 0.1% by mass or less than 0.01% by mass.

[0062] The composite particles may also contain any other materials (including unavoidable impurities).

[0063] Based on the total mass of the composite particles, the amount of silicon atoms in the composite particles (e.g., the total amount of Si atoms in all silicon-containing materials, such as the Si phase, silicon oxide phase, and magnesium silicide oxide phase) is, for example, 20% or more by mass and less than 95% by mass, 30% or more by mass and less than 80% by mass, or 50% or more by mass and less than 70% by mass.

[0064] Based on the total mass of the composite particles, the amount of magnesium atoms in the composite particles (e.g., the total amount of Mg atoms in all magnesium-containing materials, such as magnesium oxide phase, magnesium oxide (MgO) phase, and metallic magnesium (Mg) phase) is, for example, 0.1% by mass or more and 20% by mass or less, 0.5% by mass or more and 10% by mass or less, or 1% by mass or more and 5% by mass or less.

[0065] The average particle size of the composite particles is, for example, 100 nm or more and 20 µm or less, preferably 200 nm or more and 15 µm or less, and more preferably 500 nm or more and 10 µm or less. In this specification, "average particle size" refers to the particle size at 50% of the cumulative particle size distribution measured by laser diffraction scattering, i.e., the median diameter (D50).

[0066] carbon coating

[0067] The composite particles may be coated with a carbon-based material. Hereinafter, the coating of the carbon-based material will be referred to as a "carbon coating". In this specification, "coated with a carbon-based material" means that at least a portion of the outer surface of the particles is physically covered by the carbon-based material. Other materials (e.g., other coatings) may exist between the outer surface of the particles and the carbon-based material coated on the outer surface of the particles.

[0068] Carbon coatings can impart electrical conductivity to composite particles. Furthermore, when the surface of composite particles is coated with carbon-based materials, side reactions between the composite particles and other materials (such as electrolytes) can be suppressed. Additionally, the carbon-based coating can absorb the expansion of the Si phase, thereby inhibiting cracking.

[0069] Carbon materials used for carbon coatings may include: graphite such as natural graphite and artificial graphite; carbon fibers such as mesophase carbon microspheres (MCMB), carbon nanotubes and carbon nanofibers; carbon black such as Ketjen black, Denka black and acetylene black; graphene or graphene oxide; or mixtures thereof.

[0070] Based on the amount of composite particles (excluding the carbon coating), the amount of carbon coating formed on the composite particles is, for example, 5% by mass or more and 20% by mass or less, preferably 6% by mass or more and 18% by mass or less, and more preferably 8% by mass or more and 15% by mass or less. When the amount of carbon coating is 5% by mass or more, side reactions between the composite particles and other materials can be suppressed. When the amount of carbon coating is 20% by mass or less, a battery capacity above a predetermined level can be obtained, and the agglomeration of composite particles can be suppressed by carbon deposition. However, the amount of carbon is not limited to the above range. When the amount of carbon is outside the above range, the battery performance may decrease slightly, but this does not affect its function as a rechargeable battery.

[0071] The carbon coating covers, for example, 50% to 100%, 60% to 99%, or 70% to 95% of the surface area of ​​the composite particles. The average thickness of the carbon coating formed on the surface of the composite particles can be, for example, 10 nm to 10 µm, 50 nm to 5 µm, 100 nm to 2 µm, or 200 nm to 1 µm.

[0072] adhesives

[0073] The adhesive is added to facilitate the adhesion of the active material to the conductive agent or current collector. Examples of adhesives may include, but are not limited to, polyvinylidene fluoride (PVdF), polyvinyl alcohol (PVA), polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), polyacrylic acid, acrylamide, polyimide, fluororubber, or copolymers thereof.

[0074] Based on the total mass of the negative electrode active material layer, the amount of adhesive can be from 0.1% to 30% by mass. The amount of adhesive is preferably 0.5% by mass or more and 20% by mass or less, more preferably 1% by mass or more and 10% by mass or less. When the amount of adhesive falls within the above range, sufficient adhesion within the electrode can be provided while preventing capacity decay in the battery.

[0075] conductive agent

[0076] Conductive agents are not limited to a specific type and can include any conductive material that does not cause a chemical change. Examples of conductive agents may include, but are not limited to, one or more of the following: carbon-based materials (e.g., artificial graphite, natural graphite, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, carbon black, acetylene black, Ketjen black, Denka black, thermally cracked carbon black, channel black, furnace black, lamp black, and carbon fiber), metal powders or metal fibers (e.g., aluminum, tin, bismuth, silicon, antimony, nickel, copper, titanium, vanadium, chromium, manganese, iron, cobalt, zinc, molybdenum, tungsten, silver, gold, lanthanum, ruthenium, platinum, and iridium), conductive whiskers (e.g., zinc oxide and potassium titanate), conductive metal oxides (e.g., titanium oxide), and conductive polymers (e.g., polyaniline, polythiophene, polyacetylene, polypyrrole, and polyphenylene derivatives).

[0077] Based on the total mass of the negative electrode active material layer, the amount of conductive agent can be from 0.1% by mass to 30% by mass. The amount of conductive agent is preferably 0.5% by mass or more and 15% by mass or less, more preferably 0.5% by mass or more and 10% by mass or less. When the amount of conductive agent is within the above range, sufficient conductivity can be imparted, and the amount of negative electrode active material will not decrease, thereby ensuring battery capacity.

[0078] Thickener

[0079] The negative electrode active material slurry used to coat the negative electrode active material onto the negative electrode current collector may contain a thickener. Specifically, the thickener may include a cellulose compound, such as carboxymethyl cellulose (CMC). For example, the content of the thickener may be more than 0.5% by mass and less than 10% by mass based on the total mass of the negative electrode active material layer.

[0080] solvent

[0081] The solvent used in the negative electrode active material slurry is not limited to a specific type and may include any type of solvent commonly used in the manufacture of negative electrodes. Examples of solvents may include, but are not limited to, one or a mixture of N-methyl-2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO), isopropanol, acetone, water, or water.

[0082] 1-1-2. Manufacturing method of negative electrode

[0083] The method for manufacturing a negative electrode for a lithium-ion secondary battery according to the embodiments includes the following steps: (1) Preparation of negative electrode active materials (2) Preparation of negative electrode active material slurry from negative electrode active material (3) The negative electrode is manufactured from the negative electrode active material slurry. (1) Steps for preparing negative electrode active materials Step (1) in preparing the negative electrode active material can be "a method for preparing the negative electrode active material". The method for preparing the negative electrode active material includes the following steps.

[0084] (a) Making silicon dioxide (SiO) a The reduction step of the reaction between magnesium (Mg) and metal (0 < a ≤ 2).

[0085] (b) Acid treatment steps for the material obtained after the reaction of (a) with acid.

[0086] (c) Mechanical alloying of the material obtained after the reaction of (a) until the crystallite size is less than 10 nm as evaluated by powder XRD pattern.

[0087] The preparation method of negative electrode active material may also include the following steps.

[0088] (d) Coating steps of coating the material obtained after the reaction of (a) with carbon-based materials.

[0089] (a) Restoration steps

[0090] In the reduction step, metallic magnesium (Mg) acts as a reducing agent. For example, silicon dioxide (SiO₂) is considered to be a reducing agent. a The chemical reaction between ) and metallic magnesium (Mg) proceeds as follows.

[0091] SiO a + aMg → Si + aMgO

[0092] In the reduction step, as described above, silicon dioxide (SiO2) is preferred. a ) is completely or as much as possible reduced to Si. When silicon oxide (SiO) is reduced to Si. a When the Si phase is completely or as much as possible reduced to Si, the amount of Si phase participating in the charge-discharge reaction within the composite particles can be increased, thereby improving the energy density of the secondary battery.

[0093] The silicon dioxide used as a raw material can be, for example, SiO2. a Powder with (0 < a ≤ 2) SiO a It can have a Si phase The structure of (Si particles) dispersed in an amorphous or crystalline manner within an amorphous silicon oxide matrix. Here, the Si phase and the silicon oxide matrix are collectively referred to as silicon oxide (SiO₂). aThat is, 'a' is the average value of the Si phase and the silicon oxide matrix. Here, 0 < a ≤ 2, preferably 0.5 ≤ a ≤ 1.6, and more preferably 0.8 ≤ a ≤ 1.5. For example, the silicon oxide in the raw material is silicon monoxide (SiO) (a=1) or silicon dioxide (SiO2) (a=2). Furthermore, the silicon oxide powder in the raw material may include SiO with a specific 'a' value. a Or two or more SiO2 species with different a values a A mixture of powders.

[0094] Meanwhile, in the reduction step, the initial components contained in silicon oxide (SiO2) a The Si phase in the composite particles can undergo crystal growth, increasing its crystallite size. For example, the crystallite size of the Si phase in the composite particles immediately after the reduction step can be greater than 10 nm, 50 nm, or 100 nm. However, with the increase in the crystallinity of the Si phase, the degree of expansion and contraction of the Si phase during charge and discharge may increase, thus adversely affecting the cycle characteristics. Therefore, the crystallite size of the Si phase can be reduced again in the mechanical alloying step described below.

[0095] The average particle size of the silica particles in the raw material is, for example, 100 nm or more and 20 µm or less, preferably 200 nm or more and 10 µm or less, and more preferably 500 nm or more and 5 µm or less. When the average particle size is smaller, there are more reaction sites in the charge-discharge reaction, resulting in higher battery capacity. When the average particle size is 100 nm or more, the energy density can be increased to some extent. When the average particle size is 20 µm or less, the lifetime characteristics caused by volume expansion can be suppressed.

[0096] In the reduction step, the mass ratio of Si atoms to Mg atoms (Si / Mg) is 0.1 or more and 3 or less, preferably 0.3 or more and 2.5 or less, more preferably 0.5 or more and 2 or less, even more preferably 0.6 or more and 1.8 or less, and even more preferably 0.8 or more and 1.5 or less. When the mass ratio (Si / Mg) is 0.1 or more, a certain level of energy density can be obtained by using a predetermined amount of Si to drive the charge-discharge reaction. When the mass ratio (Si / Mg) is 3 or less, sufficient reduction reaction leads to a significant improvement in battery capacity.

[0097] Furthermore, magnesium silicide oxides can be produced as byproducts of the reaction between silicon oxide and metallic magnesium (Mg) or magnesium oxide (MgO). Examples of magnesium silicide oxides include MgSiO3 and Mg2SiO4.

[0098] The reaction conditions include any conditions used for the above-described reaction. From a simplicity and ease of handling perspective, it is preferable to mix silica powder with magnesium (Mg) powder and then heat it; however, this method is not limited to this, for example, the materials can react in solution. The reduction reaction is preferably carried out under an inert gas (nitrogen, argon) atmosphere or a reducing atmosphere. The reaction temperature is, for example, 500°C or higher and 1000°C or lower, preferably 600°C or higher and 900°C or lower, more preferably 650°C or higher and 850°C or lower, and even more preferably 700°C or higher and 800°C or lower. The reaction pressure is not limited to a specific range. The reaction time is, for example, 10 minutes or more and 3 hours or less, preferably 30 minutes or more and 2 hours or less.

[0099] It is speculated, for example, that the mechanism of the reduction reaction is as follows. However, the following description is based on speculation, and the present invention is not limited by theory.

[0100] When silica particles in the raw material react with metallic magnesium (Mg), the silica is reduced to Si. Simultaneously, magnesium oxide (MgO) or magnesium silicide oxide is formed. As a result, composite particles are obtained that are a homogeneous, integrated, and / or combined composition of silicon (Si), magnesium oxide (MgO), magnesium silicide oxide, and unreacted metallic magnesium (Mg). However, when the reduction reaction is incomplete, in addition to the above components, the composite particles may also contain residual silica matrix that has not been reduced to the Si phase. In this case, some Si phase may be discontinuously dispersed within the silica matrix.

[0101] (b) Acid treatment steps

[0102] In the acid treatment step, magnesium oxide (MgO) and / or unreacted metallic magnesium (Mg) generated in the reduction step can be removed by reacting with acid. Therefore, the decrease in energy density or initial efficiency caused by MgO or Mg can be suppressed. Specifically, magnesium oxide (MgO) and unreacted metallic magnesium (Mg) react with acid to generate magnesium ions (Mg²⁺). 2+ Magnesium ions (Mg) 2+ It can be removed by washing with water, resulting in the removal of magnesium oxide (MgO) and unreacted metallic magnesium (Mg).

[0103] MgO + 2H + → Mg 2+ + H2O

[0104] Mg 2+ + 2H + → Mg 2+ + H2

[0105] The acid may not include acids that strongly dissolve silicon oxide (SiOx), such as hydrofluoric acid (HF).

[0106] The acid treatment step involves adding an acid to the product of the reduction step. The acid is, for example, an aqueous solution of an acid. The aqueous solution of the acid is, for example, an aqueous solution of a strong acid. The strong acid may include inorganic or organic acids, such as hydrochloric acid, nitric acid, sulfuric acid, hydrobromic acid, hydroiodic acid, sulfonic acid, or combinations thereof. That is, the acid treatment step may include a process of reacting the material obtained after the reduction step with at least one acid selected from the group consisting of hydrochloric acid, nitric acid, sulfuric acid, hydrobromic acid, hydroiodic acid, and sulfonic acid. For example, when hydrochloric acid is used, the following chemical reaction occurs between magnesium oxide (MgO) and metallic magnesium (Mg) and hydrochloric acid.

[0107] MgO + 2HCl → MgCl2 + H2O

[0108] Mg + 2HCl → MgCl2 + H2

[0109] The concentration of the aqueous acid solution is, for example, 0.1 M or more and 10 M or less, preferably 0.5 M or more and 5 M or less. When the concentration is 0.1 M or more, impurities can be sufficiently removed. When the concentration is 10 M or less, sufficient manufacturing efficiency can be maintained. The amount of aqueous acid solution added per 1 g of composite particles obtained in the reduction step is, for example, 1 mL or more and 100 mL or less, preferably 5 mL or more and 80 mL or less, more preferably 10 mL or more and 50 mL or less. When the concentration of the aqueous acid solution is 1 M, the amount of acid added per 1 g of composite particles is, for example, 1 mmol or more and 100 mmol or less, preferably 5 mmol or more and 80 mmol or less, more preferably 10 mmol or more and 50 mmol or less.

[0110] The reaction conditions include any conditions used for the above-described reaction. The reaction temperature is, for example, 10°C or higher and 90°C or lower, preferably 10°C or higher and 50°C or lower. The reaction pressure is not limited to a specific range. The reaction time is, for example, 1 hour or higher and 48 hours or lower, preferably 6 hours or higher and 36 hours or lower, more preferably 12 hours or higher and 30 hours or lower.

[0111] Due to its low reactivity with acids, at least some magnesium silicide oxide may remain after acid treatment; however, depending on the raw materials, acid, or reaction conditions used, all or part of the magnesium silicide oxide may decompose. To reduce the oxide phase and improve initial efficiency, it is preferable to increase the reaction time to ensure adequate treatment.

[0112] After reacting with acid, the acid-dissolved material can be removed by conventional washing. Composite particles can be obtained through a washing and drying process.

[0113] (c) Mechanical alloying steps

[0114] In the mechanical alloying step, the crystallinity of at least one crystalline phase in the composite particles can be reduced by mechanically alloying the composite particles. Specifically, the crystallite size of the crystalline phase in the composite particles can be reduced before and after mechanical alloying. The crystallite size can be evaluated from the peak width of the powder XRD pattern using the Scherrer equation.

[0115] In this specification, "mechanical alloying" refers to mechanical stirring of the sample using grinding. Mixing is used to impart energy to the sample. Through grinding, impact energy or shear energy is applied to the composite particles, resulting in a reduction in the crystallite size of the crystalline phase within the composite particles. When the crystallite size of the Si phase decreases, the degree of expansion and contraction of the Si phase during charge and discharge can be suppressed. Furthermore, when the crystallite size of magnesium oxide silicide (e.g., MgSiO3 and / or Mg2SiO4 phase) decreases, the grain boundaries between the Si phase and magnesium oxide silicide may decrease, thereby suppressing intraparticle cracking caused by the expansion and contraction of the Si phase during charge and discharge.

[0116] Grinding methods may include ball mills, stirred mills using rotating rods, and any other grinding apparatus. For example, the mechanical alloying can be carried out by at least one method selected from the group consisting of planetary mills, rotary mills, vibratory mills, electric mills, and stirred mills. For example, when using a ball mill, composite particles and a suitable amount of balls are placed in a container, and the container is rotated or vibrated. The impact energy generated by collisions between balls or between balls and the wall can cause breakage, deformation, and / or changes in the internal structure of the composite particles (e.g., decomposition of microcrystals in the composite particles).

[0117] The balls used in ball mills are not limited to a specific size, shape, or material. Balls can include small balls (beads) corresponding to what are called bead mills. Furthermore, the balls are not limited to spherical shapes and can have any other shape, such as angular shapes. Zirconia is commonly used as a material for the balls, but the materials for the balls are not limited to this and can include any other material.

[0118] The grinding conditions can be appropriately set according to the material or properties of the composite particles. For example, grinding conditions may include room temperature (e.g., above 0°C and below 50°C), a rotation speed of 100 rpm and below 1000 rpm, and a processing time of 1 hour and below 24 hours. Under given grinding conditions, the number of balls can be determined to control the crystallite size of at least one phase in the composite particles to below 10 nm. For example, when the mass of the negative electrode active material is 100 parts by mass, the amount of balls may be above 1000 parts by mass and below 10000 parts by mass, above 1500 parts by mass and below 5000 parts by mass, or above 2000 parts by mass and below 4000 parts by mass.

[0119] Mechanical alloying can be performed under an inert atmosphere. When mechanical alloying is performed under an inert atmosphere, the re-oxidation of the reduced silicon oxide during the reduction step can be prevented.

[0120] Following mechanical alloying, the resulting particles can undergo post-processing. Post-processing may include at least one process selected from crushing, sieving, chemical modification of the particles, and additive treatment. For example, the particle size of the composite particles after mechanical alloying can be adjusted by crushing and / or sieving.

[0121] The acid treatment and mechanical alloying steps are not limited to a specific order, but mechanical alloying after acid treatment has the advantages described below. When MgO and / or Mg are removed from composite particles by acid treatment, voids may form at the sites where MgO and / or Mg are removed. Due to the repeated expansion and contraction of the Si phase caused by the charge-discharge reaction, these voids may lead to cracking within the composite particles. However, it is believed that when mechanical alloying of the composite particles is performed after acid treatment, the composite particles can be compressed inward or fractured at the void sites, just like the voids, thereby suppressing cracking caused by voids in the final electrode. That is, the mechanical alloying step may include the process of compacting the void-containing particles.

[0122] (d) Coating step

[0123] Optionally, the resulting composite particles may undergo a coating step. In this coating step, the composite particles are surface-coated with a carbon-based material. The carbon coating process can be performed using any commonly used carbon coating method, and is not limited to any particular method. Carbon coating methods may include dry and wet methods. Examples of dry methods may include depositing carbon onto the composite particles via chemical vapor deposition (CVD). Examples of wet methods may include mixing a carbon source with the composite particles in a solution and then heating and drying the mixture.

[0124] For example, when carbon deposition is performed using CVD, it is preferable to perform the process at a relatively low temperature for a long time to ensure that the surface of the composite particles is fully coated with carbon. For example, the carbon deposition temperature is 500°C or higher and 900°C or lower, preferably 600°C or higher and 800°C or lower. For example, the carbon deposition time is 10 minutes or higher and 24 hours or lower, preferably 30 minutes or higher and 10 hours or lower, more preferably 1 hour or higher and 2 hours or lower.

[0125] Steps (b) through (d) are not limited to the above order and can be performed in any other order.

[0126] (2) Steps for preparing negative electrode active material slurry from negative electrode active material

[0127] A solvent is added to the negative electrode active material obtained in (1). In this case, a conductive agent, a binder, and a thickener may optionally be added. When the negative electrode active material, the conductive agent, the binder, and the thickener are dissolved or dispersed in the solvent, a negative electrode active material slurry is obtained.

[0128] (3) Steps for manufacturing the negative electrode from the negative electrode active material slurry

[0129] The negative electrode active material slurry can be coated onto the negative electrode current collector, then dried and rolled to obtain a negative electrode with a negative electrode active material layer on the negative electrode current collector.

[0130] Alternatively, for example, a negative electrode active material slurry can be applied to a carrier by casting, a film can be peeled off from the carrier, and the film layer can be pressed onto the negative electrode current collector to manufacture the negative electrode. Furthermore, any other method can be used to form a negative electrode active material layer on the negative electrode current collector, and the negative electrode active material is not limited to slurry form.

[0131] 1-2. Positive electrode

[0132] 1-2-1. Components of the positive electrode

[0133] In the lithium-ion secondary battery of the embodiment, the positive electrode includes a positive current collector and a positive active material layer formed on one or both sides of the positive current collector. The positive active material layer may exist on all or part of the surface of the positive current collector.

[0134] Positive current collector

[0135] The positive current collector used for the positive electrode is not limited to a specific type and can be any material that does not cause chemical changes and is conductive in the battery. For example, the positive current collector can include: stainless steel; aluminum; nickel; titanium; sintered carbon; aluminum or stainless steel with a surface treated with carbon, nickel, titanium or silver.

[0136] The thickness of the positive current collector can range from 3 μm to 500 μm. The positive current collector can have a finely textured surface to improve adhesion to the positive electrode active material. The positive current collector can be in various forms, such as films, sheets, foils, meshes, porous bodies, foams, or nonwoven fabrics.

[0137] Positive electrode active material layer

[0138] The positive electrode active material layer can be formed, for example, by coating a slurry of positive electrode active material, a conductive agent, and a binder, which is dissolved and dispersed in a solvent, onto the positive electrode current collector, followed by drying and rolling. Optionally, the mixture may contain any other additives, such as dispersants or fillers.

[0139] Based on the total mass of the positive electrode active material layer, the content of the positive electrode active material can be from 80% to 99% by mass.

[0140] Positive electrode active material

[0141] The positive electrode active material may include compounds capable of reversibly inserting and deintercalating lithium. Specific examples may include, for instance, lithium metal composite oxides containing at least one metal selected from cobalt, manganese, nickel, copper, vanadium, and aluminum, and lithium. More specifically, lithium metal composite oxides may include: lithium manganese oxides (e.g., LiMnO2, LiMnO3, LiMn2O3, LiMn2O4); lithium cobalt oxides (e.g., LiCoO2); lithium nickel oxides (e.g., LiNiO2); lithium copper oxides (e.g., Li2CuO2); and lithium vanadium oxides (e.g., LiV3O8); lithium nickel manganese oxides (e.g., LiNi... 1-z Mn z O2 (0 < z < 1), LiMn 2-z Ni z O4 (0 < z < 2)); lithium nickel cobalt oxides (e.g., LiNi 1-y Co y O2 (0 < y < 1)); lithium manganese cobalt oxides (e.g., LiCo) 1-z Mn z O2 (0 < z < 1), LiMn 2-y Co y O4 (0 < y < 2)); lithium nickel manganese cobalt oxides (e.g., Li(Ni) x Co y Mn z )O2(0<x<1, 0<y<1, 0<z<1, x+y+z =1), Li(Ni x Co y Mn z )O4(0<x<2,0<y<2,0<z<2,x+y+z =2)); Lithium-nickel-cobalt-metal (M) oxides (e.g., Li(Ni) x Co y Mn z M w O2 (M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and 0 < x < 1, 0 < y < 1, 0 < z < 1, 0 < w < 1, x + y + z + w = ​​1)); and compounds in which the transition metal element in the listed compounds is partially replaced by one or more other metal elements. The positive electrode active material layer may include any one of these or a compound thereof, but is not limited thereto.

[0142] In particular, regarding the improvement of battery capacity characteristics and stability, preferred positive electrode active materials include LiCoO2, LiMnO2, LiMn2O4, LiNiO2, and lithium nickel manganese cobalt oxides (e.g., Li(Ni)O2). 1 / 3 Mn 1 / 3 Co 1 / 3 O2, Li(Ni) 0.6 Mn 0.2 Co 0.2 O2, Li(Ni) 0.4 Mn 0.3 Co 0.3 O2, Li(Ni) 0.5 Mn 0.3 Co 0.2 O2, Li(Ni) 0.7 Mn 0.15 Co 0.15 O2, Li(Ni) 0.8 Mn 0.1 Co 0.1 O2), lithium nickel cobalt aluminum oxide (e.g., Li(Ni) 0.8 Co 0.15 Al 0.05 O2).

[0143] Adhesives and conductive agents

[0144] The type and amount of binders and conductive agents used in the positive electrode active material slurry can be the same as those used in the negative electrode.

[0145] solvent

[0146] The solvent used in the positive electrode active material slurry is not limited to a specific type and may include any type of solvent commonly used in the manufacture of positive electrodes. Examples of solvents may include, but are not limited to, amine solvents (e.g., N,N-dimethylaminopropylamine, diethylenetriamine, N,N-dimethylformamide (DMF)), ether solvents (e.g., tetrahydrofuran), ketone solvents (e.g., methyl ethyl ketone), ester solvents (e.g., methyl acetate), amide solvents (e.g., dimethylacetamide and 1-methyl-2-pyrrolidone (NMP)), dimethyl sulfoxide (DMSO), or a mixture thereof.

[0147] The solvent content is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, taking into account the slurry coating thickness or manufacturing yield, and has a viscosity that ensures high thickness uniformity during the coating process on the positive electrode current collector.

[0148] 1-2-2. Manufacturing method of positive electrode

[0149] The method for manufacturing a positive electrode for a lithium-ion secondary battery according to the embodiments may include the following steps: dissolving or dispersing a positive electrode active material and optionally a binder, a conductive agent and a thickener in a solvent to obtain a positive electrode active material slurry, and coating the positive electrode active material slurry onto a positive electrode current collector in the same manner as the method for manufacturing a negative electrode to form a positive electrode active material layer on the positive electrode current collector, thereby obtaining a positive electrode.

[0150] 1-3. Diaphragm

[0151] In the lithium-ion secondary battery embodiments, the separator can be, but is not limited to, any separator commonly used in lithium-ion secondary batteries to separate the negative electrode from the positive electrode, thereby providing a path for the movement of lithium ions. In particular, preferred separators may have low resistance to the movement of electrolyte ions and high electrolyte wettability. For example, the separator may comprise a porous polymer membrane made of polyolefin polymers (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, or ethylene / methacrylate copolymer), or a stacked structure of two or more layers thereof. Alternatively, the separator may comprise a porous nonwoven fabric, such as a nonwoven fabric made of high-melting-point glass fiber or polyethylene terephthalate fiber. Furthermore, to ensure heat resistance or mechanical strength, ceramic or polymer-coated separators may be used.

[0152] 1-4. Non-aqueous electrolytes

[0153] In the non-aqueous electrolyte secondary battery of the embodiment, the non-aqueous electrolyte may include, but is not limited to, organic liquid electrolyte, inorganic liquid electrolyte or solid electrolyte used to manufacture the secondary battery.

[0154] Non-aqueous electrolytes may contain organic solvents and lithium salts, and optionally, may also contain additives. In the following text, liquid electrolytes are referred to as “electrolytes”.

[0155] Organic solvents are not limited to a specific type and can include any type of organic solvent capable of serving as a medium for the movement of ions participating in the electrochemical reactions of the battery. Examples of organic solvents can include, but are not limited to, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether solvents such as dibutyl ether and tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitrile solvents such as R-CN (where R is a hydrocarbon group having a linear, branched or cyclic structure from C2 to C20 and may contain exocyclic double bonds or ether bonds); amide solvents such as dimethylformamide; dioxolane solvents such as 1,3-dioxolane; and sulfolane solvents.

[0156] Lithium salts are not limited to a specific type and may include any compound capable of providing lithium ions for lithium-ion secondary batteries. Examples of lithium salts may include, but are not limited to, one or a mixture of LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. For example, the concentration of lithium salt contained in the electrolyte may be greater than 0.1 mol / L and 2 mol / L. Below L. When the concentration of lithium salt is within the above range, the electrolyte exhibits optimal conductivity and viscosity, resulting in high electrolyte performance, thereby enabling efficient movement of lithium ions.

[0157] Additives may be optionally included to improve battery life characteristics, inhibit battery capacity decay, and improve battery discharge capacity. Examples of additives may include, but are not limited to, one or mixtures thereof, such as halogenated alkylene carbonates (FEC) or difluoroethylene carbonate (DFEC), pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol ethers, hexamethylphosphoric triamine, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol, and aluminum trichloride. For example, the content of the additive may be from more than 0.1% by mass to less than 15% by mass based on the total mass of the electrolyte.

[0158] 2. Manufacturing method of non-aqueous electrolyte secondary battery

[0159] The non-aqueous electrolyte secondary battery of the embodiment can be manufactured by placing the negative and positive electrodes separated by a separator and an electrolyte. For example, the non-aqueous electrolyte secondary battery can be manufactured by placing the negative and positive electrodes separated by a separator to form an electrode assembly, placing the electrode assembly in a battery case (e.g., a cylindrical battery case or a prismatic battery case), and injecting electrolyte. Alternatively, after stacking the electrode assembly, the non-aqueous electrolyte secondary battery can be manufactured by placing the electrode assembly filled with electrolyte into a battery case and sealing the battery case. However, the method of manufacturing the non-aqueous electrolyte secondary battery is not limited to the above examples, and any other method can be used.

[0160] The battery casing can include any battery casing commonly used in this art. The shape of the battery casing can include, for example, a cylindrical, prismatic, pouch-shaped, or snap-shaped casing, similar to a can.

[0161] The lithium-ion secondary battery of the embodiment can be used not only as a power source for small devices, but also as a unit cell in medium to large-sized battery modules that include multiple battery cells. Preferred examples of medium to large-sized devices may include, but are not limited to, electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems.

[0162] 3. Effects

[0163] When silicon-based materials are used as negative electrode active materials to improve the capacity of lithium-ion secondary batteries, using pure silicon (Si) results in very low cycle performance due to cracking caused by expansion during charging. Therefore, commercially available negative electrode active materials containing a mixture of small amounts of silicon monoxide and graphite are available. Silicon monoxide has a Si phase dispersed within SiO₂, which helps to suppress the expansion of Si. x The composite structure in the phase matrix. However, the use of silicon monoxide (SiO) induces irreversible lithium silicate phase formation during initial charging, resulting in a discharge capacity significantly lower than the charge capacity, leading to an extremely low initial efficiency of 65% to 70%. For this reason, it is difficult to achieve a balance with the initial efficiency of the cathode material when the amount of silicon monoxide (SiO) in the anode material increases.

[0164] To address the aforementioned issues, the inventors sought to reduce the silicate phase by reducing silicon oxide to improve capacity and initial efficiency. However, as mentioned above, reduction treatment may increase the crystallinity of the Si phase, leading to a higher likelihood of electrode expansion. Furthermore, the high crystallinity of each crystalline phase may create sharper grain boundaries within the negative electrode active material, making it more difficult for the matrix phase to absorb the expansion of the Si phase. After careful investigation, the inventors solved this problem by reducing the crystallite size of each crystalline phase.

[0165] By utilizing the negative electrode active material of the embodiment, the reduction of silicon oxide increases the amount of the Si phase and reduces the silicate phase, which is the cause of irreversible capacity, thereby improving capacity and initial efficiency. Simultaneously, the crystallite size of less than 10 nm allows the Si phase to be dispersed within the negative electrode active material, preventing the expansion and contraction of the Si phase during charge and discharge, thus suppressing the expansion of the entire electrode. Furthermore, reducing the crystallite size may lead to a reduction or disappearance of grain boundaries, thereby preventing the expansion of the Si phase from being restricted by the interface surface. Therefore, expansion-induced cracking can be suppressed.

[0166] According to the method for preparing the negative electrode active material described in this embodiment, mechanical alloying can reduce the crystallite size of the crystalline phase in the reduced composite particles. In particular, since high-temperature reduction treatment can increase the crystallinity of the crystalline phase, mechanical alloying after reduction treatment can reduce the increased crystallinity. When the crystallinity of the crystalline phase is reduced, the aforementioned effect can be obtained from the negative electrode active material. Furthermore, in addition to the Si phase, mechanical alloying can reduce the crystallinity of magnesium silicide oxide generated during the reduction process using Mg. Reducing the crystallinity of magnesium silicide oxide leads to a decrease or disappearance of grain boundaries with the Si phase, making it easier for the Si phase to function as a matrix, thereby suppressing the volume expansion of Si. Therefore, cracking caused by the expansion and contraction of the Si phase can be suppressed, thereby improving the cycle characteristics of the secondary battery. Furthermore, all the constituent materials of the composite particles are stable in water and do not generate gas.

[0167] Example

[0168] The present invention will be illustrated by experimental examples below. However, the present invention is not limited to the following experimental examples.

[0169] Example 1

[0170] Preparation of negative electrode active materials

[0171] Silica (SiO) powder with an average particle size of 1 µm and magnesium (Mg) powder with an average particle size of 300 µm were mixed at a mass ratio of 2:1. The mixture was placed in a plasma sintering machine (from Microphase) and held at 850 °C for 1 hour under an inert gas atmosphere, where the Mg powder induced a reduction reaction in the SiO powder. Powder XRD analysis and elemental analysis confirmed that the product contained silicon (Si), magnesium (Mg), magnesium oxide (MgO), and magnesium silicide oxides (MgSiO3, Mg2SiO4).

[0172] 10 g of the product was added to 200 mL of 2 M hydrochloric acid and stirred for 36 hours to remove the Mg and MgO phases. Subsequently, it was washed and dried at 120 °C. Then, 10 g of the dried powder and 200 g of zirconia spheres were loaded into a zirconia container and mechanically alloyed under the following conditions. The particles were then removed from the container and appropriately pulverized and sieved to adjust the average particle size to 8 μm, thereby obtaining the negative electrode active material.

[0173] Conditions for mechanical alloying

[0174] • Machine used: Planetary ball mill P6 (from FRITSCH)

[0175] • Speed: 500 rpm

[0176] • Container capacity: 250 mL

[0177] • Temperature: Room temperature

[0178] • Atmosphere: Argon atmosphere

[0179] Processing time: 3 hours

[0180] Preparation of button cells

[0181] The obtained negative electrode active material, an aqueous dispersion (0.4% solids) of carbon black (CB) and single-walled carbon nanotubes (SWCNTs) as conductive materials, styrene-butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener were prepared at a mass ratio of 88.8:3.3:0.25:3.65:4.0. First, the negative electrode active material, CB, and CMC were mixed together, then the SWCNT dispersion and water were added and kneaded. Finally, SBR was added and mixed to prepare the negative electrode active material slurry.

[0182] The obtained slurry was uniformly coated onto copper foil, vacuum dried at 110°C for 10 hours, and cut into circles with a diameter of 13 mm to manufacture the negative electrode. A 2016-type coin cell was manufactured using the prepared negative electrode and lithium metal as the counter electrode. Here, when manufacturing the negative electrode, the electrode weight was recorded; this electrode weight is the mass of the negative electrode mixture material (solvent-free negative electrode active material slurry) per unit area of ​​the negative electrode. Simultaneously, the weight of the negative electrode mixture material was calculated by subtracting the weight of the current collector from the total electrode weight.

[0183] Example 2

[0184] Except for CVD treatment of the powder after mechanical alloying, the negative electrode active material and the coin cell containing the negative electrode active material were prepared by the same method as in Example 1. Specifically, the negative electrode active material obtained in Example 1 was subjected to CVD treatment with ethylene gas for 1 hour while rotating the core tube at 750°C, thereby coating the surface of the powder particles with carbon. The CVD-treated powder was appropriately pulverized and sieved to adjust the average particle size to 8 μm, thereby obtaining the negative electrode active material of Example 2. The mass ratio before and after CVD treatment confirmed that the treated product contained 10% by mass of carbon.

[0185] Comparative Example 1

[0186] Except for the plasma sintering temperature of 750°C and the omission of mechanical alloying treatment, the negative electrode active material and the coin cell containing the negative electrode active material were prepared by the same method as in Example 1.

[0187] Comparative Example 2

[0188] Except that the amount of zirconium oxide spheres in the mechanical alloying process is 100g, the negative electrode active material and the coin cell containing the negative electrode active material are prepared by the same method as in Example 1.

[0189] Comparative Example 3

[0190] Except for the plasma sintering temperature of 750°C, the CVD treatment time of 1 hour, and the omission of mechanical alloying treatment, the negative electrode active material and the coin cell containing the negative electrode active material were prepared by the same method as in Example 2.

[0191] Comparative Example 4

[0192] Except that the amount of zirconium oxide spheres in the mechanical alloying process is 100g, the negative electrode active material and the coin cell containing the negative electrode active material are prepared by the same method as in Example 2.

[0193] Evaluation Example 1: Measurement of X-ray diffraction (XRD) patterns

[0194] Figure 1 This diagram shows the powder X-ray diffraction (PXRD) patterns of the negative electrode active materials obtained in Examples 1, 2, and Comparative Example 1. In Comparative Example 1, which did not undergo mechanical alloying, a sharp peak for Si was observed at approximately 28.5°, along with peaks for MgSiO3 and Mg2SiO4. On the other hand, in Examples 1 and 2, which underwent mechanical alloying, broadening of the peaks in the XRD patterns was observed. The crystallite size of each sample was evaluated using the Scherrer equation based on the peak linewidth. In Examples 1 and 2, no peak for Mg2SiO4 was observed, indicating that Mg2SiO4 was in a completely amorphous state.

[0195] Evaluation Example 2: Initial Characteristics of the Battery

[0196] The coin cells of the Examples and Comparative Examples were each charged and discharged at a constant current of 0.2C with a cutoff voltage of 1.5V. "Initial capacity" was defined as the value obtained by dividing the discharge capacity in the first charge-discharge cycle by the mass (g) of the negative electrode active material used in the Examples and Comparative Examples, respectively.

[0197] Mathematical Formula 1

[0198] In addition, the charge-discharge efficiency during the first charge-discharge cycle (hereinafter referred to as "initial efficiency") is defined as follows.

[0199] Mathematical formula 2

[0200] Evaluation Example 3: Battery Cycle Characteristics

[0201] For each coin cell manufactured according to the embodiments and comparative examples, after the initial charge-discharge process performed in Evaluation Example 2, another charge-discharge cycle was performed under the same conditions, and the same charge-discharge cycle was repeated 48 times at a constant current of 0.5C. That is, a total of 50 charge-discharge cycles, including the first and second charge-discharge cycles, were repeated. Figure 2 This is a graph showing the cycle characteristics of coin cells from Example 1, Comparative Example 1, and Comparative Example 2 that have not undergone CVD treatment. Figure 3 This is a graph showing the cycle characteristics of coin cells from Examples 2, 3, and 4, which underwent CVD processing. Specifically, Figure 2 and Figure 3 The graph is plotted with the discharge capacity of the button cells in the embodiments and comparative examples as the vertical axis and the number of charge-discharge cycles as the horizontal axis.

[0202] Evaluation Example 4: Battery Expansion Characteristics

[0203] For each coin cell manufactured according to the examples and comparative examples, a 51st charge cycle was performed after 50 charge-discharge cycles in Evaluation Example 3. Subsequently, the charged coin cells were disassembled, the thickness of the negative electrode was measured, and the thickness (t) of the negative electrode active material layer was measured by subtracting the thickness of the current collector from the measured value. The electrode weight (w) of the negative electrode active material recorded during the manufacture of the negative electrode (unit: g / cm³) was used to measure the thickness of the negative electrode active material layer. 2 Divide the negative electrode active material layer by its thickness (t) to calculate the density d = w / t (unit: g / cm³). 3 Furthermore, the volumetric discharge capacity C50 after 50 charge-discharge cycles is calculated by multiplying the unit mass discharge capacity (c) (unit: mAh / g) in the 50th charge-discharge cycle by the density (d) of the negative electrode active material layer. The volumetric discharge capacity C50 = c × d (unit: mAh / cm²) is calculated. 3 The C50 value incorporates two factors: the battery's cycle characteristics and the expansion characteristics of the negative electrode active material. Specifically, as the battery's cycle characteristics improve, the 50th discharge capacity (c) increases, and as the expansion of the negative electrode active material is suppressed, the density (d) of the negative electrode active material layer increases. Therefore, the C50 value increases due to either the improved cycle characteristics or the suppressed expansion of the negative electrode active material. Thus, a sufficiently large C50 value indicates a good balance between cycle characteristics and the expansion characteristics of the negative electrode active material.

[0204] The table below summarizes the results of Evaluation Examples 1 to 3 for both the Examples and Comparative Examples. Meanwhile, the discharge capacity per unit volume (C50) was normalized relative to the value 100 of Example 2 for comparison.

[0205] Table 1

[0206] As described above, in Examples 1 and 2, which involved relatively vigorous mechanical alloying using 200g of zirconia spheres, the crystallite size of Si and MgSiO3 was less than 10 nm, resulting in batteries with improved initial capacity and a volumetric discharge capacity C50 after 50 charge-discharge cycles. In Examples 1 and 2, it can be considered that not only the initial capacity but also the cycle characteristics were improved, and the expansion of the negative electrode active material was suppressed. Furthermore, it was confirmed that Example 2, which had a carbon coating treated by CVD, exhibited improved initial efficiency, cycle characteristics, and C50 compared to Example 1.

[0207] On the other hand, in Comparative Examples 1 and 3, which did not undergo mechanical alloying, the Si crystallite size was greater than 100 nm, and the initial capacity and C50 were lower than in Examples 1 and 2. Furthermore, in Comparative Examples 2 and 4, which underwent mild mechanical alloying using 100 g of zirconia spheres, the Si crystallite sizes were 65 nm and 72 nm, respectively. Figure 2 and Figure 3 As shown, it was confirmed that, compared with Comparative Examples 1 and 3 which were not mechanically alloyed, Comparative Examples 2 and 4 had a greater decrease in discharge capacity and worse cycle characteristics.

Claims

1. A negative electrode active material, comprising: Composite particles containing Si phase and magnesium silicide oxide. Wherein, the crystallite size of the Si phase and the crystallite size of at least one phase contained in the magnesium silicide oxide, as evaluated by powder X-ray diffraction patterns, are less than 10 nm.

2. The negative electrode active material as described in claim 1, in, The magnesium silicide oxide contains at least one of Mg2SiO4 or MgSiO.

3. The negative electrode active material as described in claim 1 or 2, in, The composite particles contain at least one of the Si phase or magnesium silicide oxide, which is amorphous.

4. The negative electrode active material as described in claim 1 or 2, in, Based on the total mass of the composite particles, the amount of Si phase contained in the composite particles is more than 20% by mass and less than 70% by mass.

5. The negative electrode active material as described in claim 1 or 2, in, The composite particles contain virtually no MgO.

6. The negative electrode active material as described in claim 1 or 2, in, The surface of the composite particles is coated with a carbon-based material.

7. The negative electrode active material as described in claim 6, in, Based on the amount of composite particles excluding the carbon-based material, the amount of carbon-based material coating the composite particles is 5% by mass or more and 20% by mass or less.

8. A negative electrode comprising: Negative current collector, and A negative electrode active material layer present on the negative electrode current collector, wherein the negative electrode active material layer comprises the negative electrode active material as described in claim 1 or 2.

9. A non-aqueous electrolyte secondary battery comprising the negative electrode as described in claim 8.

10. A method for preparing a negative electrode active material, comprising: silicon dioxide (SiO) a The reduction step in the reaction of magnesium (Mg) with metallic magnesium (0 < a ≤ 2); An acid treatment step involving treating the reacted material with acid; and The reacted material is mechanically alloyed until the crystallite size, as evaluated by powder X-ray diffraction, is less than 10 nm.

11. The method for preparing the negative electrode active material as described in claim 10, in, The mechanical alloying is carried out by at least one means selected from the group consisting of planetary mills, rotary mills, vibratory mills, electric mills, and stirred mills.

12. The method for preparing the negative electrode active material as described in claim 10 or 11, in, The mechanical alloying is carried out under an inert atmosphere.

13. The method for preparing the negative electrode active material as described in claim 10 or 11, in, In the acid treatment step, MgO is removed by reacting with acid.

14. The method for preparing the negative electrode active material as described in claim 10 or 11, in, In the reduction step, silicon oxide (SiO) a At least a portion of ) is reduced to Si.

15. The method for preparing the negative electrode active material as described in claim 10 or 11, further comprising: The coating step involves coating the reacted material with a carbon-based material.

Citation Information

Patent Citations

  • Negative electrode material, method of producing the negative electrode material, and mixed negative electrode material

    JP2018152250A